Transfer of Gogol Turnover Land to Freehold Land in Tuban Regency - Kholik, Kholik; Warka, Made (LEGAL BRIEF, 2024)
In terms of land ownership, the conception of national land law states that land throughout Indonesia belongs to the Indonesian nation, which is also a symbol of unity for the integrity of the nation and state, therefore it cannot be bought and sold or traded, and must not be used as an object of control that causes disintegration of the nation. One of the former Indonesian land rights (customary land) that was converted into property rights is the gogolan rights. Apart from being able to be converted into ownership rights, these gogolan rights can also be converted into use rights according to the type of right that applies. Gogol land has still been assigned land status and its rights holders based on a Joint Decree (SK) of the Minister of Home Affairs and the Minister of Agrarian Affairs converted into freehold land, while Gogol land in rotation has not had a decree issued and to date has not been regulated. The research results show that land rights that existed before the enactment of the UUPA were changed to land rights stipulated in the UUPA so that now there is only one type of land ownership right. Then the transition to the UUPA was to provide legal certainty regarding land rights for the people as a whole, through land registration institutions and statutory regulations as the legal basis for its implementation. The conversion of permanent gogolan, pekulen or sanggan rights into property rights as intended in Article VII paragraph (1) of the Conversion Provisions of the Basic Agrarian Law is carried out by means of a decision letter confirming the Head of the Agrarian Inspection concerned